PENINGKATAN KOMPETENSI GURU DALAM PENULISAN KARYA ILMIAH MELALUI PENDAMPINGAN PENELITIAN TINDAKAN KELAS - Deselia Khairunnisa, Asni; Marlina, Marlina; Fathony, Hafiz; Shafwan, Rofi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This Community Service (PKM) program aimed to enhance teachers’ competence in scientific writing through the Classroom Action Research (CAR) approach. The mentoring was conducted at MIS Darul Ma’rifah, Tanah Bumbu Regency, involving 24 teachers through lectures, discussions, Q&A sessions, and direct guidance. As a result, 80% of participants were able to independently and correctly structure CAR reports, two teachers’ manuscripts were selected as exemplary models, and the average score increased from 68.5 (pre-test) to 85.2 (post-test). Feedback indicated that the program supported teachers in formulating research problems relevant to their teaching practice and fostered a research culture in elementary schools. The unique contribution of this program compared to previous studies lies in its development of a CAR-based teacher mentoring model that integrates theoretical training, hands-on classroom practice, and continuous evaluation through online forums. This model not only improved scientific writing skills but also cultivated reflective and collaborative mindsets, making it replicable in other schools. CAR-based mentoring proved effective in strengthening teacher professionalism and improving teaching quality. ABSTRAK Kegiatan PKM ini bertujuan meningkatkan kompetensi guru dalam penulisan karya ilmiah melalui pendekatan Penelitian Tindakan Kelas (PTK). Pendampingan dilaksanakan di MIS Darul Ma’rifah, Kabupaten Tanah Bumbu, melibatkan 24 guru dengan metode penyampaian materi, diskusi, tanya jawab, dan bimbingan langsung. Hasilnya, 80% peserta mampu menyusun sistematika PTK secara mandiri dan benar, dua draft karya ilmiah guru terpilih sebagai contoh, serta terjadi peningkatan skor rata-rata dari 68,5 pada pre-test menjadi 85,2 pada post-test. Umpan balik menunjukkan kegiatan ini membantu guru merumuskan masalah penelitian relevan dari praktik mengajar dan mendorong budaya meneliti di sekolah dasar. Kontribusi unik kegiatan ini dibanding studi terdahulu adalah pengembangan model pendampingan guru berbasis PTK yang menggabungkan pelatihan teori, praktik langsung di kelas, dan evaluasi berkelanjutan melalui forum daring. Model ini tidak hanya meningkatkan keterampilan menulis ilmiah, tetapi juga membentuk pola pikir reflektif dan kolaboratif yang dapat direplikasi di sekolah lain. Pendampingan berbasis PTK terbukti efektif memperkuat profesionalisme guru dan meningkatkan mutu pembelajaran.